Nearly Zero Energy Building Refurbishment A Multidisciplinary Approach - Pacheco Torgal, Fernando; Mistretta, Marina; Kaklauskas, Artūras; Granqvist, Claes G.; Cabeza, Luisa F. (Springer London : Imprint: Springer, 2013)
The recast of the Energy Performance of Buildings Directive (EPBD) was adopted by the European Parliament and the Council of the European Union on 19 May 2010. For new buildings, the recast fixes 2020 as the deadline for all new buildings to be "nearly zero energy" (and even sooner for public buildings - by the end of 2018). This book gives practitioner an important tool to tackle the challenges of building refurbishment towards nearly zero energy. This book is welcome at this time and sets the scene for professionals whether practitioners or researchers to learn more about how we can make whether old or new buildings more efficient and effective in terms of energy performance. .